2019
DOI: 10.1111/wrr.12720
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory levels of B‐cell activating factor of the TNF family in patients with diabetic foot ulcer: Association with disease progression

Abstract: Enhanced and prolonged expression of tumor necrosis factor alpha (TNF-α), a potent pro-inflammatory cytokine is evidenced during the chronic wound healing process of infected diabetic foot ulcer (IDFU). B-cell activating factor (BAFF) is the member of TNF-α family, which implicit in B-cell dysfunction. This study was aimed to evaluate the role of BAFF in diabetic foot ulcer (DFU) patients and to correlate its association with other family of inflammatory cytokines. Circulating levels of BAFF and other cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…CRP is a marker of inflammation and is involved in the innate immune signal. 69 There are a few studies that reported decreased serum CRP to be associated with improvement in various chronic wounds, 70 being positively correlated with progressive infected diabetic ulcers, 71 , 72 and being correlated with amputation of diabetic foot ulcers. 73 In the current research, serum CRP and wound exudate CRP are correlated, which does not report the association between CRP and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a marker of inflammation and is involved in the innate immune signal. 69 There are a few studies that reported decreased serum CRP to be associated with improvement in various chronic wounds, 70 being positively correlated with progressive infected diabetic ulcers, 71 , 72 and being correlated with amputation of diabetic foot ulcers. 73 In the current research, serum CRP and wound exudate CRP are correlated, which does not report the association between CRP and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, B-cell-activating factor (BAFF), as a member of the TNF superfamily, is involved in infected diabetic foot ulcers. The elevation of BAFF in this condition has been correlated with an increased level of pro-inflammatory cytokines such as IL-26 [54]. Diabetic retinopathy is another diabetes-related pathologic condition that is considered a sight-threatening disease.…”
Section: Other Hypersensitivity Conditionsmentioning
confidence: 99%
“…The release of inflammatory factors can alter the stability of the internal environment of the foot and aggravate the infection. 5,6 Therefore, there is an urgent need to identify relevant biomarkers to promote the early detection of DF.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with DM, the infected foot induces an inflammatory reaction, promoting the release of inflammatory factors in multiple tissues and organs. The release of inflammatory factors can alter the stability of the internal environment of the foot and aggravate the infection 5,6 . Therefore, there is an urgent need to identify relevant biomarkers to promote the early detection of DF.…”
Section: Introductionmentioning
confidence: 99%